2019
DOI: 10.1038/s41598-019-53997-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern and molecular signature of cholinergic tuft cells in human gastro-intestinal and pancreatic-biliary tract

Abstract: Despite considerable recent insight into the molecular phenotypes and type 2 innate immune functions of tuft cells in rodents, there is sparse knowledge about the region-specific presence and molecular phenotypes of tuft cells in the human digestive tract. Here, we traced cholinergic tuft cells throughout the human alimentary tract with immunohistochemistry and deciphered their region-specific distribution and biomolecule coexistence patterns. While absent from the human stomach, cholinergic tuft cells localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 66 publications
(96 reference statements)
3
89
0
5
Order By: Relevance
“…To evaluate Hpgds protein expression, we conducted multiplex immunofluorescence for Hpgds and tuft cell marker phospho-EGFR on metaplasia and PanINbearing human pancreatitis samples (5). Though rare, we found that 100% of pancreatitis tuft cells (30/30; n=3 patients) express Hpgds at the protein level ( Figure 6C), consistent with studies in normal human pancreas (19). We then conducted eicosanoid profiling on PDA (n=6) and nearby normal pancreas (n=3) ( Figure S14A, File S5), but were unable to include human PanIN due to lack of available fresh tissue.…”
Section: Pancreatic Tuft Cells In Human Disease Tuft Cells Are Also supporting
confidence: 83%
See 1 more Smart Citation
“…To evaluate Hpgds protein expression, we conducted multiplex immunofluorescence for Hpgds and tuft cell marker phospho-EGFR on metaplasia and PanINbearing human pancreatitis samples (5). Though rare, we found that 100% of pancreatitis tuft cells (30/30; n=3 patients) express Hpgds at the protein level ( Figure 6C), consistent with studies in normal human pancreas (19). We then conducted eicosanoid profiling on PDA (n=6) and nearby normal pancreas (n=3) ( Figure S14A, File S5), but were unable to include human PanIN due to lack of available fresh tissue.…”
Section: Pancreatic Tuft Cells In Human Disease Tuft Cells Are Also supporting
confidence: 83%
“…These studies suggest that tuft cells play multifaceted roles in sensing and responding to diverse infectious and inflammatory conditions. While tuft cells have been reported in rat and human pancreas, they are not normally present in the murine pancreas (5,19). Rather, we and others showed that tuft cells transdifferentiate from the acinar cell epithelium as part of ADM in response to oncogenic Kras expression (5,20).…”
mentioning
confidence: 52%
“…The discrepancy also occurs in the biliary tract. ChAT + cholinergic tuft cells have been found in extra-hepatic peribiliary glands but are absent in gall bladder and common bile duct epithelium in human ( Schütz et al, 2019 ), whereas they scatter throughout the gall bladder and extra-hepatic bile duct in rodents ( Schütz et al, 2015 ). It’s not confusing that tuft cells should not be defined into one single lineage because of the multiple characteristics and wide dispersal throughout mucosal surfaces.…”
Section: Characteristics Of Tuft Cellsmentioning
confidence: 99%
“…Recently, Schütz et al (2019) identified the distribution and molecular signatures of cholinergic tuft cells in human digestive tract, including gastrointestinal, biliary and pancreatic systems. Given that tuft cell is the only epithelial cellular source of ACh in human digestive tract ( Schütz et al, 2019 ), tuft cell-derived cholinergic signaling may play a considerable role and should be paid more attention. In the light of this rationale, this review, summarizing older reviews and novel advances, focuses on the pathophysiological roles of tuft cell derived ACh.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have shown that TCs also release acetylcholine to signal to surrounding cell types. These cholinergic TCs are selectively distributed in interlobular ducts in the middle of the pancreas and may play an important role in the immune processes of infection and cancer [10].…”
Section: Tuft Cells As a Therapeutic Target For Pancreatitis And Pdacmentioning
confidence: 99%